Mechanical properties and failure modes of recycled polypropylene/microcrystalline cellulose composites - Zulkifli, Nur Izzati; Samat, Noorasikin; Anuar, Hazleen; Zainuddin, Norhazlin (Elsevier, 2015)
The effects of microcrystalline cellulose (MCC) fibre on the properties of recycled polypropylene (rPP)composites were investigated. A coupling agent, maleic anhydride grafted-polypropylene (MAPP) was used to improve the interfacial adhesion between the MCC fibres and rPP matrix. A series of rPP/MCC composites, with or without MAPP, were compounded with an extruder and then moulded with an injection moulding machine. It was found that without MAPP, an increase in MCC loadings caused degradation in the tensile strength of rPP composites. However, the impact strength was higher compared to that of neat rPP prior to its decrease caused by the increase in MCC loading. All mechanical properties showed improvement after MAPP was added, especially in tensile modulus. FESEM morphology also revealed better interfacial adhesion between the MCC fibres and the rPP matrix. Fracture analysis indicated that the ductile and quasi-brittle behaviours in both types of rPP/MCC composites (with or without MAPP) were affected by the concentration of fibres and the interfacial adhesion strength.